Norwegian perspectives on education and cultural diversity - Kulbrandstad, Lars Anders (Cambridge Scholars Publishing, 2018)
This collection of articles utilises thematic orientations, methodological approaches and data materials to give an insight into the opportunities and challenges that exist for education in society, in relation to the growing cultural and linguistic complexity that exists. It is written by researchers at Inland Norway University of Applied Sciences, in Norway, and while the book is anchored in a specific Norwegian educational, cultural and political context, it addresses issues that would be of interest to an international academic audience.